Current Therapeutic Options for the Treatment of Juvenile Idiopathic Arthritis - Saougou, Ioanna G.; Markatseli, Theodora E.; Voulgari, Paraskevi V.; Drosos, Alexandros A. (Current Rheumatology Reviews, 2021)
Juvenile idiopathic arthritis (JIA) is a chronic inflammatory disease and an exclusion diagnosis that includes all forms of arthritis that persists for more than 6 weeks under the age of 16. Although there is not yet a cure for JIA, and recent advances in the therapeutic field have created a more hopeful present and future for the patients. In the past, therapies for JIA have depended on non-steroidal medication, conventional synthetic disease-modifying antirheumatic drugs and corticosteroids. However, over the last decades, the advent of biologic therapies in JIA contributed to the preservation of functional activity, control of pain, avoidance of joint damage, and extra-articular manifestations. Furthermore, over the last years, international institutions, such as the American College of Rheumatology, have released recommendations and guidelines for rheumatologists for optimal JIA management. All the above have revolutionized the treatment of JIA with promising outcomes. To this end, the relevant literature is reviewed and discussed appropriately.
Keywords: treatment